Management beyond Insulin in Gestational Diabetes Mellitus: A Review Update (Journal of National Institute of Neurosciences Bangladesh, 2018)
Hyperglycemia is the most common endocrine disorder of pregnancy. As compared to Diabetes in pregnancy(DIP) the management of gestational DM(GDM) has always been a topic of controversy. Medical nutrition therapy(MNT) is the cornerstone of GDM management. 80-90% of GDM mothers can be treated by MNT alone and the rest will require drugs. Considerable controversy surrounds the use of oral anti-diabetic medications in pregnancy. The most widely studied drugs are glyburide and metformin. Conflicting results have been produced by different studies. However recent meta-analyses have shown that they can be an attractive alternative to insulin if long term safety data become available. Till then it might be too early to make a final comment on their use in GDM.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 145-149